Broilers fed with cayeno (Hibiscus rosa-sinensis) flour (Revista Sistemas de Producción Agroecológicos, 2016)
This work was carried out in Villavicencio (Meta), with the purpose of studying the inclusion of different levels of flour of Hibiscus rosa-sinensis (CAF) (0, 5, 8 and 12%) in diets for chickens fattening, partly replacing traditional use other foods, mainly meat meal and soybean meal. The statistical design used was a completely randomized with four treatments, three replications and 10 experimental units in each replication (4 x 3 x 10 = 120 birds). Was evaluated weight gain, consumption, alimentary conversion, protein biological value (BV), protein efficiency ratio (PER), digestibility of neutral detergent fiber (NDF) and carcass yield. The biggest daily gain by bird (P
Keywords: poultry; shrubby; fiber; supplement